Authentic learning situations for the evaluation of competencies at the initial level - Joya Donayre, Patricia Andrea (2019)
The purpose of this article is to present the importance of promoting authentic situations of student learning  based on contextualization, as well as the evaluation of skills at the initial level. It compiles literature review regarding authentic situations or tasks, key concepts and principles to be taken into account for the identification of authentic situations, from the purpose to the resources to be used.